A multi-plant production planning model considering non- repeated setup and aperiodic shipment. (October 2020) - Shen, Guangya; Luo, Kaiping; Li, Liheng
Highlights: A new multi-plant production planning model is proposed. Both non-repeated setup and aperiodic shipment are formulated. The properties of the proposed model have been developed. The significance of backorder is investigated. The limitation of shipment at a time is discussed. Abstract: A new model for multi-plant production planning is developed. As the important actual features of some manufacturers, non-repeated setup and aperiodic shipment are appropriately introduced into the multi-plant production planning model and the corresponding constraints are accurately linearized. The new model is also applicable in the case of periodic shipment or backorder prohibition. Its effectiveness is examined by an instance which simulates many real characteristics. The experimental results indicate that the new model achieves the optimal profit. The sensitivity of unit setup cost and unit shipment cost is analyzed. The significance of backorder and the limitation of shipment at a time are discussed in detail.